Discourse features of outstanding inventors’ biographies in English - Vương Văn Kiều (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study is aimed at investigating the discourse features of outstanding inventors' biographies in English (EOIBs). The four aspects of discourse feature under investigation were layout features, syntactic structures, lexical choices, and cohesive devices. The study was conducted based on the combination of a variety of methods such as descriptive, analytic, and inductive ones. The data for analysis in this thesis are 43 samples of EOIBs which are gathered from reliable electronic newspapers specializing in writing biographies of famous people around the world. In terms of layout, EOIBs could be divided into four sections: the Headline; the Introduction and the Illustration; the Storyline; and the Conclusion with different elements in each section are the four main components of outstanding inventors’ biographies in English. With regard to the syntactic features, the passive voice, the direct and indirect speeches, and relative clauses were investigated. An indispensable part of writing EOIBs is the lexical choices. In this term, the result of the research shows the use of pronouns, expressions, and verbs. Finally, with respect to cohesive devices, grammatical cohesion and lexical cohesion were investigated. The former includes personal reference, additive conjunction, and repetition. The result revealed that these three types of cohesion were the devices employed with high frequencies in EOIBs. It is hoped that the findings of this thesis can, to some extent, provide a better understanding of biographies in the light of discourse analysis for Vietnamese teachers who teaches English and college or university students majoring in the English language in general or those who are interested in the discourse of biographies in particular.